Risk factors associated with pulmonary tuberculosis. - Tissera, P.A.D (My University, 1994)
The principle objective of this case-control study was to identify some demographic,socioeconomical and biological factors associated with pulmonary tuberculosis.93 cases of pulmonary TB in patients aged 30 years and above,presenting at the chest clinic,Galle,was compared with age,sex,matched same number of controls admitted to surgical units at teaching hospital,Karapitiya,during the same period of time.There was statistically significant association between tuberculosis and education level (P0.01)(Table 5.6).However education level of grade 8 and lower was not found to be a risk factor associated with TB in age group 60 and above(p0.05)(Table 5.20).There was statistically significant association between TB and income level (P0.001)(Table 5.9).However monthly income of equal or less than Rs.3000/0.05)(Table 5.16).The bivariate analysis,revealed areas of residence as a risk factor in age group 30-59 years(OR=2.5,P0.05)(Table 5.19) and exsmoker and smokers as a risk factor in age group 60 years and above.